Organizational strategy, higher education advocacy and effective academic leadership in a Malaysian research university. - Shahmandi, Elham; Silong, Abu Daud; Farid, Hadi; Abu Samah, Bahaman (2011)
Which skills or abilities are more related to academic leaders to become more effective? This study focuses on the investigation of effective academic leadership styles. In the present situation of globalization, academic excellence is often related to being Research University. Estimates of leadership effectiveness are obtained from multiple regressions. These estimates are based on four leadership styles that include telling, selling, participating, and delegating styles. The predictors of leadership effectiveness are higher education advocacy and organizational strategy. Results shows that academic leaders prefer to utilize different leadership styles based on contributions of both predictors. To summarize, effective academic leaders make use various leadership competencies according to certain situations. Based on the findings organizational strategy is significantly related to telling style and higher education advocacy is significantly related to selling, participating, and delegating styles.